2013
DOI: 10.1007/s00467-013-2417-8
|View full text |Cite
|
Sign up to set email alerts
|

Two dosing regimens for steroid therapy in nephrotic syndrome

Abstract: Dear Editor, We read with great interest the article entitled "Weight or body surface area dosing of steroids in nephritic syndrome: is there an outcome difference?" by Saadeh et al. which was recently published in Pediatric Nephrology [1].In this article, the authors concluded that dosing of steroids per body surface area (BSA-based dosing) is superior to dosing per kilogram body weight (BW-based dosing) in terms of reducing the frequently relapsing course rate in nephritic syndrome (NS) patients. Although th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…These latest observations by Hirano and Fujinaga [1] further support the need to better understand the effect of different dosing regimens on the initial and subsequent outcome of nephrotic syndrome-questions which will be better answered by larger, randomized prospective trials.…”
Section: Sirmentioning
confidence: 84%
See 1 more Smart Citation
“…These latest observations by Hirano and Fujinaga [1] further support the need to better understand the effect of different dosing regimens on the initial and subsequent outcome of nephrotic syndrome-questions which will be better answered by larger, randomized prospective trials.…”
Section: Sirmentioning
confidence: 84%
“…We read with great interest the letter sent to your journal by Hirano and Fujinaga [1] in which they describe a retrospective review of children with idiopathic nephrotic syndrome (NS) weighing 30 kg or less at their institution. Based on their results, they concluded that the onset time for relapses after initial therapy was significantly shorter for children in the body weight (BW)-based dosing group than those in the body surface area (BSA)-based group.…”
Section: Sirmentioning
confidence: 99%
“…Calculation using body weight is convenient, but results in relative underdosing, particularly in young children [47,49]. Underdosing, using weight-based calculations, was associated with increased risk of frequent relapses in some [50,51], but not in all studies [52,53]. Experts therefore prefer to administer prednisolone based on body surface area for young children [47].…”
Section: Rationalementioning
confidence: 99%
“…The result was decreased clinical response compared with a larger dose determined by body surface area. [14][15][16] Analogously, usual doses of prednisolone used in studies concluding no benefit from corticosteroids in preschool-aged children with acute viral-respiratory infection-induced exacerbations also may have been confounded by suboptimal dosage.…”
Section: To the Editormentioning
confidence: 99%